Policy Monitoring and Ministerial Survival: Evidence from Multiparty Presidentialism. Issue 1 (20th January 2022) - Silva, Thiago N.; Medina, Alejandro
Abstract : Studies on policy monitoring and ministerial survival within coalition governments are usually conducted separately. In this study, we bring these topics together and argue that the strategy of coalition partners to oversee the implementation of one another's policies has surprising consequences on the duration of office‐holding ministers. Our main theoretical insight suggests that the degree to which ministers behave as faithful agents of the government depends on their expectations about their partners' monitoring behavior, such that when they expect to be under high scrutiny, they moderate their drifting behavior. Using evidence from legislative information requests on the activities of individual ministers over all multiparty cabinets formed in Brazil between 1995 and 2014, we demonstrate that: (1) greater policy monitoring by coalition partners is observed under more ideologically heterogeneous cabinets, and (2) more frequent policy‐monitoring efforts by coalition partners lead to a lower ministerial replacement within the government term.